Tailored ZnO Functional Nanomaterials for Solution‐Processed Quantum‐Dot Light‐Emitting Diodes - Saeedeh Mokarian Zanjani; Francesco Tintori; Sadra Sadeghi; Pavel Linkov; Sergey Dayneko; Afshin Shahalizad; Hamid Pahlevaninezhad; Majid Pahlevani (Advanced Photonics Research, 2022)
Recent improvements in efficiency and luminance of quantum‐dot light‐emitting diodes (QLEDs) promise a versatile technology for next‐generation lighting and display applications. This is accomplished due to the advances in colloidal quantum‐dot (CQD) synthetic methods together with proper engineering of the charge balance in these devices. The exciton quenching mechanisms occurring at the interface between the QD emissive layer and the zinc oxide (ZnO) electron transport layer (ETL) are one of the important parts of the charge transport path, affecting efficiency and long‐term stability. Herein, a comprehensive overview of the advances in the engineering of ZnO‐based ETLs, in terms of device efficiency and operational stability, is attempted. It is specifically highlighted that significant improvements can be achieved using various ZnO ETL defect passivation methods. This review also describes the key requirements for high‐performance QLEDs from the ETL engineering aspect and catalyzes for further interdisciplinary explorations to realize reliable devices for practical applications.